Fault tolerant power converter topologies for PMSM drives in aerospace applications - Khwan-on, Sudarat; De Lillo, Liliana; Lee, Empringham; Wheeler, Patrick W.; Gerada, Christopher; Othman, Md Nazri; Jasim, Omar; Clare, Jon (Institute of Electrical and Electronics Engineers Inc., 2009)
This paper proposes two fault tolerant power converter permanent magnet synchronous motor (PMSM) drive topologies. A reconfigured conventional DC link/two-level VSI converter and a reconfigured conventional matrix converter are presented to improve the reliability of the drive system under open phase fault operating condition. Additional phase redundancy and its control technique are included. Simulation and experimental results are shown to verify the effectiveness of the proposed topologies.